PNEUMOCOCCAL INFECTIONS AS MODERN THREAT TO HEALTH OF EARLY AGE CHILDREN: VACCINATION PROSPECTS - E.F. Lukushkina (Union of pediatricians of Russia, 2009)
Wide spread of pneumococcal carriage, resistance to human organism defenses and ease of developing antibiotic resistance makes pneumococcus an extremely significant pathogen. Pneumococcal infections pose a serious threat to children's population - approximately 1 million children die of pneumococcal infections annually. The new technology for producing vaccines through conjugation of proteins to polysaccharide has opened up a possibility of effective immunization against pneumococcal infection, providing immediate protection and creating immunological memory. Evidence of safety of applying conjugated pneumococcal vaccine was obtained through extensive research conducted both in the USA and Europe. Scheduled immunization of children provides significant medical and social, and therefore, an economic benefit by reducing the morbidity rate both in children and in adults.Key words: pneumococcal infection, vaccination, pneumococcal conjugated 7-valent vaccine, children.